2020
DOI: 10.1002/lt.25852
|View full text |Cite
|
Sign up to set email alerts
|

Center Variation in Intention‐to‐Treat Survival Among Patients Listed for Liver Transplant

Abstract: In the United States, centers performing liver transplant (LT) are primarily evaluated by patient survival within 1 year after LT, but tight clustering of outcomes allows only a narrow window for evaluation of center variation for quality improvement. Alternate measures more relevant to patients and the transplant community are needed. We examined adults listed for LT in the United States, using data submitted to the Scientific Registry of Transplant Recipients. Intention-to-treat (ITT) survival was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Similar to prior studies, we found that the greatest variation in bMELD‐predicted mortality risk was observed among candidates with MELD 26–30. In an analysis that followed transplant recipients from the time of listing, the variation in 1‐year waitlist mortality across transplant centers was 20.6%–28.8%, greater than post‐transplant mortality variation, and more varied (53%–72.1%) among candidates with MELD ≥ 25 27 . The rare transplant centers and circumstances that have a relatively higher‐than‐average waitlist mortality risk likely warrants targeted investigation rather than radical changes to MELD‐based allocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to prior studies, we found that the greatest variation in bMELD‐predicted mortality risk was observed among candidates with MELD 26–30. In an analysis that followed transplant recipients from the time of listing, the variation in 1‐year waitlist mortality across transplant centers was 20.6%–28.8%, greater than post‐transplant mortality variation, and more varied (53%–72.1%) among candidates with MELD ≥ 25 27 . The rare transplant centers and circumstances that have a relatively higher‐than‐average waitlist mortality risk likely warrants targeted investigation rather than radical changes to MELD‐based allocation.…”
Section: Discussionmentioning
confidence: 99%
“…among candidates with MELD ≥ 25. 27 The rare transplant centers and circumstances that have a relatively higher-than-average waitlist mortality risk likely warrants targeted investigation rather than radical changes to MELD-based allocation.…”
Section: Ajtmentioning
confidence: 99%
“…This policy void sets the stage for potential wide variability in center‐level patient selection for SHK. Indeed, center level differences pertaining to patient selection in solid‐organ transplantation are well‐described, 1–11 including in simultaneous liverkidney (SLK) transplantation 12 prior to the implementation of standardized SLK criteria in 2017 13 . To our knowledge, differences in center level practice of SHK transplantation have not yet been described.…”
Section: Introductionmentioning
confidence: 99%
“…This policy void sets the stage for potential wide variability in center-level patient selection for SHK. Indeed, center level differences pertaining to patient selection in solid-organ transplantation are well-described, [1][2][3][4][5][6][7][8][9][10][11] including in simultaneous liverkidney (SLK) transplantation 12 prior to the implementation of standard-…”
mentioning
confidence: 99%
“…Kwong et al address a key metric to compare transplant centers: 1‐year posttransplant survival. ( 2 ) Although this undoubtedly is an important individual patient outcome, it does not provide a complete picture of a center’s ability to guide wait‐listed patients to transplant. Furthermore, tight clustering of 1‐year posttransplant survival data makes it difficult to ascertain individual center quality.…”
mentioning
confidence: 99%